2018
DOI: 10.1111/cch.12565
|View full text |Cite
|
Sign up to set email alerts
|

The Cellie Coping Kit for Children with Injury: Initial feasibility, acceptability, and outcomes

Abstract: Preliminary research suggests that the Cellie Coping Kit for Children with Injuries is a feasible, low-cost, preventive intervention, which may provide families with strategies to promote recovery from paediatric injury. Future research, including a randomized controlled trial, ought to further examine targeted long-term intervention outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…Thus, the intervention can offer a low-cost avenue for medical teams to provide some initial support to children with EoE and their families, while requiring minimal additional time from the medical teams. Also consistent with other Cellie Coping Kit intervention studies (e.g., Marsac et al, 2018;Cole et al, 2017), a few children and caregivers indicated that the materials had too many words or were confusing. It may be that some families would benefit from intervention materials that are less reading focused, are aimed for a lower reading level, or that use more non-verbal techniques such as visual schedules or pictures of challenges and solutions.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the intervention can offer a low-cost avenue for medical teams to provide some initial support to children with EoE and their families, while requiring minimal additional time from the medical teams. Also consistent with other Cellie Coping Kit intervention studies (e.g., Marsac et al, 2018;Cole et al, 2017), a few children and caregivers indicated that the materials had too many words or were confusing. It may be that some families would benefit from intervention materials that are less reading focused, are aimed for a lower reading level, or that use more non-verbal techniques such as visual schedules or pictures of challenges and solutions.…”
Section: Discussionsupporting
confidence: 82%
“…Although parents have been involved in early interventions after child trauma, the primary goal of these interventions was to minimise long-term psychological problems in the child (e.g. De Young, Haag, Kenardy, Kimble, & Landolt, 2016;Kramer & Landolt, 2011;Marsac et al, 2018). Extending programs by specifically targeting parents' psychological reactions as well, may enhance positive outcomes in both children and parents.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Building on promising findings from pilot studies [25], the current RCT goals represent an important next step in the advancement of the Cellie Coping Intervention for Injury. The strengths and potential positive outcomes of implementing a waitlist control RCT design with multiple informants are numerous.…”
Section: Discussionmentioning
confidence: 99%
“…95% of parents would recommend it to others) and most reported learning new skills (e.g. how to facilitate a conversion about the injury) [25]. The trial described here will provide initial data on the intervention’s impact on proximal and longer-term health outcomes.…”
Section: Cellie Coping Kit For Children With Injury Intervention Descmentioning
confidence: 99%
See 1 more Smart Citation